MATERI DAKWAH DALAM LIRIK LAGU “IZINKAN AKU REGUK CINTAMU” KARYA EBIET G ADE - A. Choiriyah (Wardah, 2015)
The material dakawah contained in the lyrics Ebiet G Ade entitled " Izinkanlah aku reguk cintamu” consists of ( 1 ) material about aqidah ( 2 ) material about the need to fear the punishment of God ( 3 ) material about the worship of God in the form of zikir, rukuk, sujud,  praising God and asking forgiveness to  Allah and ( 4 ) the material of our love to Allah and the love of Allah to us..